'The ultimate cross-cultural fertilizer': the irony of the 'transnational local' in Anglo-German rural revivalism. Issue 6 (2nd November 2019) - Stone, Dan
ABSTRACT: This article analyses the transfer of 'ruralist' ideas between Germany and Britain, showing how connections can be made across time and space between fascist(ic) ideologies of landscape and rural belonging. Focusing mainly on two individuals who bridged the countries, Rolf Gardiner and Georg Götsch, the author shows that this key aspect of fascism – ironically, one which depended so much on images that glorified 'local beauty' – drew on a store of ideas common to much of Europe at the time. Transnational history thus brings new understandings to fields even as well-researched as fascism, returning us to the truism that fascism constituted a modern movement with a combination of technocratic and scientistic as well as nostalgic and romantic elements. Indeed, the history of fascism forces us to reconsider what is meant by 'modern' in a transnational context, taking us beyond simple dualisms such as 'reactionary' and 'avant-garde' or 'futurist' and 'nostalgic'.